IDOL: Retrofit-Kotlin Service-Based Online Digital Library Application and College Open Data Repository - Taufiq Iqbal; Muhammad Wali (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2022)
Digital libraries promise new social benefits, especially for e-learning in the age of digital technology. Integrated Online Digital Libraries are required to have professional knowledge and information on one service. Digital library innovation still needs to be researched regarding initiation; development; application; exploitation; the role of the external competitive environment; the role of the organization's internal environment; and products, services, and process outcomes. In the research, the Integrated Digital Online Library – IDOL application developed will fulfill every feature of the digital library system where four core concepts (Content, User, Functionality, Quality, Policy, and Architecture) as the core model of IDOL need to be considered in relation to four main and interrelated factors. interact with the developed digital library system, and special studies are still needed on this development research. This research focuses on the development of the Integrated Digital Online Library – IDOL by implementing Retrofit-Kotlin as a highly secure REST-client library for Java and Android. The RAD (Rapid Application Development) method is used in the development process of this platform. The results of this study still need further development, both regarding functionality, interactive and collaborative web various functions are still needed. Regarding user feedback, both the interface is a factor that must be considered in future development. Regarding data speed, we adopted the HTTP/2 protocol as a data loading strategy and the IDOL platform has successfully implemented the use of Retrofit-Kotlin. Based on the test results, the level of failure in the UT-7, UT-8, and UT-10 tests with achievements of less than 80% of respondents failed to answer. For a success rate above 80% on UT-1, UT-2, UT-3, UT-4, UT-5, UT-6, and UT-9 tests